M2M Uplink Priority Scheduling Algorithm Based on Dynamic Grouping - JIN Yeqi, XU Youyu, ZHENG Min, TAN Chong, WANG Hong (Ji suan ji gong cheng, 2019)
Based on the Delay Tolerance Remaining Time(DTRT),an uplink priority scheduling algorithm for dynamic grouping of traffic is proposed.A Resource Block(RB) allocation method with variable size is adopted to satisfy the adjacency constraints of RB,and a hybrid automatic polling mechanism is introduced to solve the unfair scheduling problem of low priority traffic.Simulation results show that the system throughput of this algorithm is increased by 15% and 41% compared with PF algorithm and RR algorithm respectively,and it has better performance in terms of traffic delay and traffic differentiation.